2019
DOI: 10.1108/imds-06-2018-0245
|View full text |Cite
|
Sign up to set email alerts
|

The involvement paradox

Abstract: Purpose Can mobile instant messaging (MIM) make people entering into the state of cognitive absorption (CA)? The purpose of this paper is to investigate whether CA can help explain users’ satisfaction during the process of MIM, while interactivity and interest are operated as determinants of CA as well as directly associated with satisfaction. Design/methodology/approach This study proposes a satisfaction model that is adapted from the CA theory to investigate MIMs users’ satisfaction with two determinants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
(105 reference statements)
1
5
0
Order By: Relevance
“…We find that possessing high levels of SI and SDL can enhance learners’ experience, which in turn increases their willingness to continue with the podcast English learning. This is closely similar to the findings of Hong et al (2016) and Hou et al (2019), whereby SI is a determinant of CA in an online learning system. In addition, the effectiveness of SDL can help improve students’ language proficiency (Lee et al , 2017).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We find that possessing high levels of SI and SDL can enhance learners’ experience, which in turn increases their willingness to continue with the podcast English learning. This is closely similar to the findings of Hong et al (2016) and Hou et al (2019), whereby SI is a determinant of CA in an online learning system. In addition, the effectiveness of SDL can help improve students’ language proficiency (Lee et al , 2017).…”
Section: Discussionsupporting
confidence: 89%
“…They also found that users’ interests affect satisfaction. Hou et al (2019) stated individual interest and SI have positive effects on CA within the LINE chat app. Cheng (2022) showed that SI has positive effects on behavioral attitudes toward online virtual museum navigation.…”
Section: Hypotheses and Research Frameworkmentioning
confidence: 93%
See 3 more Smart Citations